2008
DOI: 10.1021/la703813f
|View full text |Cite
|
Sign up to set email alerts
|

Completely Dispersible PEGylated Gold Nanoparticles under Physiological Conditions:  Modification of Gold Nanoparticles with Precisely Controlled PEG-b-polyamine

Abstract: A novel water-soluble, biocompatible polymer, poly(ethylene glycol)-block-poly((2-N,N-dimethylamino)ethyl methacrylate) (PEG-b-PAMA), possessing controlled molecular weight with a narrow molecular weight distribution, was synthesized by the atom-transfer radical polymerization (ATRP) method. PEG-b-PAMA having a short PAMA chain length was successfully synthesized under suitable polymerization conditions. Gold nanoparticles (GNPs) were modified using PEG-b-PAMA prepared under a variety of PEGylation conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 49 publications
6
79
0
1
Order By: Relevance
“…We have already confirmed the usefulness of the oligoamine anchor 15,16,26,27,56,[72][73][74][75][76] instead of the sulfanyl group anchor [77][78][79] for molecular immobilization on gold surfaces and developed polyamineended PEG-modified gold surfaces using PEG-block-poly [2- Densely PEG-chain-tethered biointerface Y Nagasaki platform for ssDNA immobilization and detection; 73 in our scheme, PEG-b-PAMA was immobilized onto the gold surface followed by treatment with a ssDNA-SH, resulting in the formation of ssDNA-SH/ PEG-b-PAMA co-immobilized gold surface.…”
Section: Construction Of Oligodna/peg Hybrid Surfaces and Their Perfosupporting
confidence: 53%
See 3 more Smart Citations
“…We have already confirmed the usefulness of the oligoamine anchor 15,16,26,27,56,[72][73][74][75][76] instead of the sulfanyl group anchor [77][78][79] for molecular immobilization on gold surfaces and developed polyamineended PEG-modified gold surfaces using PEG-block-poly [2- Densely PEG-chain-tethered biointerface Y Nagasaki platform for ssDNA immobilization and detection; 73 in our scheme, PEG-b-PAMA was immobilized onto the gold surface followed by treatment with a ssDNA-SH, resulting in the formation of ssDNA-SH/ PEG-b-PAMA co-immobilized gold surface.…”
Section: Construction Of Oligodna/peg Hybrid Surfaces and Their Perfosupporting
confidence: 53%
“…In this study and our companion article, 80 we reported for the first time the direct observations of homogeneous/ inhomogeneous distributions of PEG and polyamine segments in the polymer layers on flat gold surfaces, where polyamine segments functioned as an anchor for molecular immobilization on the surface and at least six units of amine groups were needed for the strong chemisorption of polyamine on a gold substrate. 26 Using PEG-b-PMA block copolymers with different chain lengths, we then prepared an ssDNA/PEG-b-polyamine hybrid surface on a gold surface. It is interesting to note that the PEG-b-PAMA modification increased the amount of immobilized ssDNA-SH on the gold surface to 2-5 times as much as that on a bare gold surface, where the effective and selective detection of the complementary ssDNA was accomplished by the ssDNA-SH/PEG-b-PAMA (5k/5k) co-immobilized surface.…”
Section: Construction Of Oligodna/peg Hybrid Surfaces and Their Perfomentioning
confidence: 99%
See 2 more Smart Citations
“…To further characterize the state of the polymer on the GNP surface, commercial GNPs were modified using PEG-b-PAMA prepared under various PEGylation conditions [49]. In alkaline media (pH > 10) and with a [N]/[GNP] ratio above 3300, the dispersions of PEGylated GNPs were highly stable against coagulation.…”
Section: Preparation Of Bioenvironmentally Applicable Gold Nanoparticmentioning
confidence: 99%